Food insecurity, HIV/AIDS pandemic and sexual behaviour of female commercial sex workers in Lagos metropolis, Nigeria - John Lekan Oyefara (Taylor & Francis Group, 2007)
This study examined the role of hunger and food insecurity in the sexual behaviour of female commercial sex workers in Lagos metropolis, Nigeria within the context of HIV/AIDS. In addition, the study investigated the prevalence of sexually transmitted infections (STIs) and induced abortion among the respondents. Cross-sectional survey and in-depth interview research methods were adopted to generate both quantitative and qualitative data from the respondents. Findings of the study showed that 35.0% of the respondents joined the sex industry because of poverty and lack of other means of getting daily food. While all the respondents had knowledge about the existence of HIV/AIDS, 82.0% of them identified sexual intercourse as a major route of HIV transmission. There was a significant relationship between poverty, food insecurity and consistent use of condoms by female sex workers at P<0.01. Specifically, only 24.7% of the respondents used condoms regularly in every sexual act. Consequently, 51.6% had previous cases of STIs. The most prevalent STI among the respondents was gonorrhea, with 76.4% prevalence among ever infected female sex workers. This was followed by syphilis with a prevalence of 21.1%. In addition, 59.1% of the sample had become pregnant while on the job and 93.1% of these pregnancies were aborted through induced abortion. In conclusion, hunger and malnutrition were the factors that pushed young women into prostitution in Nigeria and these same factors hindered them from practicing safe sex within the sex industry. Thus, it is recommended that the Nigerian government should develop programmes that will reduce hunger and food insecurity, in order to reduce rapid transmission of HIV infection in the country.